Dari ‘illah ke maqasid: formula dinamisasi hukum Islam di era kekinian melalui pengembangan konsep maqasid - Abad Badruzaman (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2014)
This article has been pushed by the fact that the reading of classical texts does not involve the conciousness that the texts present not in a hollow space, but in a chamber having its own language, culture, values, social institutions and other patterns of social relations. This is a pure library study; all data sources are in the form of written materials related to the topic that has been set. Then these concepts, with the help of modern literature, are developed in line with the present context. Three things formulated in this study are: the concept of ‘illah, maqasid, and the development of maqasid concepts in order to make Islamic law remain dynamic. The content and the range of meaning of each of the five maqasid formulated by al-Syatibi can bedeveloped due to the demands of the present context. Therefore, the development of content and range of meaning is carried out by this paper. The author put a great effort to put a number of Qur’anic verses as the guide and giver of moral messages. Themes such as religious freedom, the maintenance of natural resources from exploitation and extermination, gender equality, nourishing the generations from neglect, oppression and poverty, and must enable the common sense in all things, in the opinion of the author are able to fill all of the content as well as expand the range of concepts of maqasid in the contemporary era.